(untitled) (Medico Legal Update, 2020)
This paper aims to analyze the factors which cause the violation of the Governmental Decree No. 6 of 2012 on Cattle Control at Palu City by cattle owners. This research was conducted at South Palu, especially at the North Birobuli District using the qualitative-naturalistic method. The results of this research show that the society has not yet obeyed the Regional Decree No. 6 of 2012 on Cattle Control at Palu City area due to some factors: (1) the new values of the Regional Decree No. 6 of 2012 is against the old values of the cattle owners; (2) the cattle owners do not have an understanding of the stipulations which apply nor do they understand the social change which is currently happening; (3) The attitudes and behaviors of the policeofficers and the changemakers were inconsistent and rather discriminative; and (4) the disobedience may cause health problems which are anthrax, nail and mouth disease, or other diseases to the cattle.